2015
DOI: 10.1159/000431036
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution of Myasthenia Gravis in Northern Europe - Results from a Population-Based Study from Two Countries

Abstract: Objectives: To compare the prevalence of myasthenia gravis (MG) subgroups based on immunological markers and clinical presentation in two geographically complete MG populations in northern Europe. Methods: This cross-sectional study included all living MG patients in Norway and a regional cohort from the Netherlands. Patients were identified using their hospital registration codes. Medical charts of subjects >16 years were reviewed. Inclusion criteria were clinical MG, a positive antibody test for acetylcholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 48 publications
8
32
1
4
Order By: Relevance
“…Similar descriptions have been sparsely reported in MG, 1,2,17,18 and the main importance of this data is to make clinicians aware of disease-associated features that need to be addressed to optimize the care of MG patients. Similar descriptions have been sparsely reported in MG, 1,2,17,18 and the main importance of this data is to make clinicians aware of disease-associated features that need to be addressed to optimize the care of MG patients.…”
Section: Discussionsupporting
confidence: 70%
“…Similar descriptions have been sparsely reported in MG, 1,2,17,18 and the main importance of this data is to make clinicians aware of disease-associated features that need to be addressed to optimize the care of MG patients. Similar descriptions have been sparsely reported in MG, 1,2,17,18 and the main importance of this data is to make clinicians aware of disease-associated features that need to be addressed to optimize the care of MG patients.…”
Section: Discussionsupporting
confidence: 70%
“…Although myasthenia gravis (MG) is a rare disease, the majority of epidemiological studies on MG are limited to national areas, whereas one previous study has compared regions from two different European countries, Norway and the Netherlands (Boldingh et al., ). The prevalence of disease‐specific antibodies is known to vary in different regions of the world, in particular the prevalence of muscle‐specific tyrosine kinase (MuSK) antibodies (Gilhus & Verschuuren, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found a different age patterns of MG patients which is due to demographic variability as well as difference in selection criteria. 18 The patients which were included in our study had a relatively shorter history of the duration of myasthenia gravis. Contrary to many other studies, the mean ± SD duration of symptoms among our patients was 5.23 ± 3.52 months which ranged within 1 month to 1 year only.…”
Section: Myasthenia Gravis (Mg) Is An Autoimmune Diseasementioning
confidence: 99%